2023
DOI: 10.1073/pnas.2220485120
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the energetic architecture within an RNA tertiary structural motif via high-throughput thermodynamic measurements

Abstract: Structured RNAs and RNA/protein complexes perform critical cellular functions. They often contain structurally conserved tertiary contact “motifs,” whose occurrence simplifies the RNA folding landscape. Prior studies have focused on the conformational and energetic modularity of intact motifs. Here, we turn to the dissection of one common motif, the 11nt receptor (11ntR), using quantitative analysis of RNA on a massively parallel array to measure the binding of all single and double 11ntR mutants to GAAA and G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 72 publications
(122 reference statements)
0
14
0
Order By: Relevance
“…In a recent set of studies, Herschlag and colleagues characterized the binding affinities of approximately 3000 tetraloop receptor mutants to the GAAA tetraloop using the RNA-MaP platform (19, 21). They identified a subset of mutations with the same binding mode as the wild-type tetraloop-receptor (11ntR).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent set of studies, Herschlag and colleagues characterized the binding affinities of approximately 3000 tetraloop receptor mutants to the GAAA tetraloop using the RNA-MaP platform (19, 21). They identified a subset of mutations with the same binding mode as the wild-type tetraloop-receptor (11ntR).…”
Section: Resultsmentioning
confidence: 99%
“…As the number of structured RNAs with potential tertiary contacts rapidly grows, there is a critical need for high-throughput methods. Greenleaf and colleagues have recently developed the RNA on a massively parallel array (RNA-MaP) platform (19)(20)(21). This device can simultaneously measure the stability of thousands of unique RNA tertiary contacts through fluorescence intensity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 11ntR, IC3R, and Vc2R (Fig. 1 A-C) were chosen to anchor our exploration of the TLR landscape due to their extensive prior study (Costa and Michel 1995;Ikawa et al 1999Ikawa et al , 2001Weinberg et al 2007;Geary et al 2008;Roth and Breaker 2009;Smith et al 2010;Bisaria and Herschlag 2015;Bonilla et al 2017Bonilla et al , 2021Shin et al 2023). We sampled the landscape spanning these receptors by investigating each stepwise sequence of mutations from the 11ntR to the two other TLRs, focusing on the shortest mutational pathways between the TLR sequences.…”
Section: Tlr Anchors and Library Designmentioning
confidence: 99%
“…1). In-depth mutational analyses revealed that the residues within the 11ntR exhibit a mix of cooperative and additive energetic properties, with cooperativity dominating proximal groups and additivity dominating groups that are distal in three-dimensional space in the TLR structure (Shin et al 2023).…”
Section: Introductionmentioning
confidence: 99%